Implementasi Kebijakan Program Bantuan Rumah Layak Huni Untuk Masyarakat Miskin di Kecamatan Long Kali - Masjaya; Burhanudin; Ismi, Anisa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to determine the implementation of the Livable Home Assistance Program policy for the poor in Long Kali District and to determine the implementation of the Livable Home Assistance Program requirements in accordance with Paser District Head Regulation Number 63 of 2019 concerning Guidelines for the Rehabilitation of Uninhabitable Houses and the Construction of Livable Houses in Paser District, especially in Long Kali District. This type of research is descriptive qualitative. Data collection techniques were carried out using observation, interviews and documentation. Data analysis used is data reduction, data display and conclusion. The results of the study show that the program for livable housing assistance for the poor has been implemented in Long Kali District, Paser Regency, seen from the outreach, evaluation and fulfillment of the requirements for livable housing assistance recipients. As well as the inhibiting factors and completion of the implementation of the Livable Housing Assistance Program policy for the poor in Long Kali District, Paser Regency, because in general each policy has optimal or non-optimal implementation.